Using Somatic, Auditory, Visual, and Intellectual (SAVI) technique to improve students’ speaking - Dahlinar Dahlinar; Sofyan Abdul Gani; Asnawi Muslem (Universitas Syiah Kuala, 2021)
The objective of this experimental study is to investigate the effect of using Somatic, Auditory, Visual, and Intellectual (SAVI) technique on students’ speaking at SMAN Model 12 Banda Aceh. Furthermore, it is also to investigate the students’ responses toward the implementation of SAVI technique in teaching speaking at SMAN Model 12 Banda Aceh. Two classes (respectively 33 students) are chosen as the sample. The students in experimental class were taught by using SAVI technique and the students in control class were taught without using SAVI technique. The data about the students’ ability were collected through giving test. Meanwhile, the students’ responses toward teaching speaking by using SAVI were collected by giving questionnaires. The data from test were analyzed by using SPSS version 23. Meanwhile the data from questionnaires were analyzed by using percentage formula suggested by Sugiyono (2015). The finding showed that using teaching speaking by using SAVI technique significantly improved students’ speaking ability, especially their speaking sub-skills. The study proved the improvement by the result of z-test in which the z-score for post-test result of experimental and control class is 3.73. It was found against the hypothesis that there is a significant difference in speaking achievement between the students who were taught by using SAVI technique and those who were taught without using SAVI technique at second year students of SMA 12 Banda Aceh.